The Oxford handbook of banking and financial history - Cassis, Youssef; Grossman, Richard S.; Schenk, Catherine R. (Catherine Ruth), 1964- (Oxford : Oxford University Press, 2016)
The financial crisis of 2008 aroused widespread interest in banking and financial history. In an attempt to better understand the magnitude of the shock, there was a demand for historical parallels. This volume provides the material for such a reflection by presenting the state of the art in banking and financial history. Contributions to this volume analyse banking and financial history in a long-term comparative perspective. Lessons drawn from these analyses may well help future generations of policy makers avoid a repeat of the financial turbulence that erupted in 2008.
General Introduction / Youssef Cassis, Richard Grossman, Catherine Schenk -- Financial History and History / Youssef Cassis -- Financial History and Financial Economics / John Turner -- Financial History and Economic Development / Gerard Caprio Jr -- Private Banks and Private Banking / Youssef Cassis -- Commercial Banking / Gerarda Westerhuis -- A Brief History of Investment Banking from Medieval Times to the Present / Caroline Fohlin -- From Multinational to Transnational Banking / Chris Kobrak -- Small-scale credit institutions / R. Daniel Wadhwani -- Money Markets / Stefano Battilossi -- Securities markets / Ranald Michie -- International Capital Flows / Moritz Schularick -- International Financial Centres / Youssef Cassis -- Monetary Systems / Angela Redish -- Central Banking / Forrest Capie -- International Cooperation and Central Banks / Harold James -- Bank Regulation and Supervision / Catherine Schenk -- State and Finance / t
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 4, 2016).
Keywords: Banks and banking -- History